POLRI : DALAM FUNGSI PENEGAKAN KETERTIBAN DAN DASAR KEHIDUPAN MASYARAKAT - FAISOL AZHARI (Unissula, 2011)
When social image for the police duty is still arround of the crime hunting only it is difficult to understand police function as an order enforcement. The success police duty is depent on two factors and they’re a police job and social image for it as an order enforcement official or namely as polisi sipil, as the best friend and also as the protector for society. The police duty should arrange/conduct social problem solving include the crime and social service for crime problem solving.Creating the order is depent on social life mode as an expert that must be achieved by police official. So that Indonesia police official is also depent on Indonesia people life include the Indonesia culture and namely as change of society.Keywords : Order, Order enforcement and change of society